Insulin pump in people with type 2 diabetes mellitus - Chlup, R. (Fundamental and Experimental Biology, 2016)
Article summarizes results of important clinical studies targeting on potential benefits of continuous subcutaneous insulin infusion (CSII) by means of an insulin pump in people with type 2 diabetes. The problems are comprised into four chapters: (1) Historical introduction; (2) Effectiveness of CSII in type 1 diabetes; (3) Influence of CSII on HbA1c and global metabolic indices in type 2 diabetes; (4) Influence of temporary CSII on beta-cell recovery in recent type 2 diabetes. Conclusion: CSII appears to be an effective part of type 2 diabetes treatment aiming to early recovery of beta cell function (if introduced without delay in a recent diabetes) and to long-lasting improvement of metabolic indices (if introduced any time of diabetes development). Adequate education of pump treated persons and their family members is necessary.